Il progetto IFRS for SMEs e le sue relazioni con le proposte di revisione delle Direttive Europee - Mattei, Marco (Piccola Impresa / Small Business, 2014)
In this paper I investigate if, in order to give a contribution to the process of accounting harmonization, the IFRS for SMEs project represents effectively a possible way forward or, contrarily, European Accounting Directives are still the best approach. As consequences, I propose an alternative solution that should be further investigated.